Adapting Stage Play to Virtual Reality Comics - Waliokar, Ved; Remedios, Delwyn Jude (ULTIMART Jurnal Komunikasi Visual, 2023)
The digital revolution has given rise to hybrid mediums and a digital culture constructed through new communication technologies. This has created opportunities for sequential storytelling to expand from its conventional form towards immersive mediums. Comics, conventionally developed in codex book form, are currently experimenting with new media tools, where screens often replace pages. This phenomenon is considered the meta-panel, which has the flexibility to take any form, shape, or size. Virtual reality comics can immerse viewers in unique ways such as immersion in a 360-degree space, ambisonic sound, motion, and interaction with the content. Studies suggest that cinematic virtual reality and stage plays have several similarities, such as long takes, exaggeration in performance, and the viewers being located at a considerable distance from the performance. Therefore, designing for virtual reality can benefit from stage methods. This study experiments with the adaptation of theatrical storytelling into comics. This paper adopts a practice-based research method to develop a virtual reality comic, The Great Golden Gang. This paper includes a discussion on the design process for developing such a virtual reality comic. To test the engagement of the virtual reality comic, Chapter One was previewed by selected participants using head-mounted displays. A participant survey demonstrates the viewer’s readiness for virtual reality comics and suggests the potential of hybrid mediums of a stage play, comics, and virtual reality. The Great Golden Gang is an example of the meta-panel and highlights the potential of virtual reality to contribute to new ways of experiencing the stage and comics. Keywords: stay-play adaptation; virtual reality; immersive comics; visual narrative